Wolfberry enhanced the abundance of Akkermansia muciniphila by YAP1 in mice with acetaminophen‐induced liver injury. Issue 1 (5th December 2022) - Liu, Yiwei; Xue, Yu; Zhang, Zhiqin; Ji, Jingmin; Li, Caige; Zheng, Kangning; Lu, Junlan; Gao, Yuting; Gong, Yi; Zhang, Yuman; Shi, Xinli
Abstract: Drug‐induced liver injury (DILI) by acetaminophen (APAP) was one of the most challenging liver diseases. Wolfberry ( Lycium barbarum L.), a traditional Chinese medicinal material and food supplement, has a potential effect on increasing the abundance of Akkermansia muciniphila ( A. muciniphila ) in mice colons. However, the effect and mechanism of wolfberry remain unclear in APAP‐induced DILI. In this study, wolfberry promoted the proliferation of activated‐ A. muciniphila in vitro and in vivo. For the first time, we detected that the activated‐ A. muciniphila but not the killed‐ A. muciniphila increased the expression level of Yes‐associated protein 1 (YAP1) in the liver and alleviated liver injury in APAP‐induced DILI mice. Mechanically, A. muciniphila improved the intestinal mucosal barrier and reduced lipopolysaccharide (LPS) content in the liver, leading to the increased expression level of YAP1. Furthermore, wolfberry increased the A. muciniphila abundance in the colon and YAP1 expression in the liver from APAP‐induced DILI mice, which promoted the recovery of APAP‐induced liver injury. Meanwhile, wolfberry combination with A. muciniphila synergistically increased AKK abundance and YAP1 expression in the liver. Our research provides an innovative strategy to improve DILI.